Starea de sănătate a populației din România în context european. O abordare din perspectiva calității vieții - Pop, Cosmina-Elena (Calitatea Vieții, 2010)
This article proposes to describe the health status of Romanian population from the quality of life perspective, using both objective and subjective indicators. The first part of this article emphasizes the health as a dimension of quality of life and the research of health using the quality of life paradigm. There are presented social factors with importance on the influence of the health status at individual and societal level. In this article, it will be analized the evolution of health status of Romanian population in the period 1990–2008, using statistical data and data provided by different national and European researches. The health status of Romanian population will be analyzed from a comparative perspective, emphasizing the position of Romanian compared to other European countries. The article relies on multiple data sources: Quality of Life Diagnosis (1990– 2006), EQLS (2007), INS, Eurostat şi TransMonee.